Pengaruh Warna Dan Material Terhadap Perancangan Rumah Bagi Manula - Andereas Pandu Setiawan, Dimas Satrio Hanindito (Intra, 2013)
Factors of concern to the elderly be family problems because of the busyness and routines. The elderly often feel ignored by family members because of the bustle of their son or grandson, and it makes the elderly feel careless, dan less communicating.The purpose of this design is to provide a temporary home for the elderly during their family members busy, which can became a new altenative for the Surabayaâs people. The concept of the design is CARE, which means giving warmth, feel save, comfort and can including all the physical and psychological differences from the elderly. The author expect the elderly can getting together and communicate with each other as well and get some entertainment or attention as long as they are in the elderly house.